Hereditary features of plasma concentrations of endothelin-1 in men with hypertension and chronic heart failure - H. O. Palahniuk; V. M. Zhebel (Zaporozhye State Medical University, 2016)
Objective. To improve diagnosis of the severity of essential hypertension in men by determining the plasma levels of ET-1 in patients with different ET-1 gene variants. Materials and methods. We examined 191 men aged 40-60 years old, who live in Podillia region in Ukraine. Among them 79 men from control group, 62 men with uncomplicated essential hypertension (EH) with left ventricular hypertrophy (LVH) and 50 men with EH and chronic heart failure (CHF) II-III functional classes by NYHA. We used clinical, biochemical, instrumental and mathematical methods of investigation, polymerase chain reaction and enzyme immunoassay. Results. In both healthy men and patients with EH Lys/Lys genotype and the Lys allele of the ET-1 gene dominates. It was found that any inherited variant of the ET-1 gene was not associated with the risk of developing EH and CHF on its background. In patients with EH the peptide level was significantly higher than in the control group and the highest concentration of ET-1 was in patients with EH and CHF. In men from the control group, patients with uncomplicated EH with LVH and EH with CHF - carriers of genotype Lys/Lys - plasma concentration of ET-1 was significantly lower than in owners of the Asn allele. In carriers of Lys/Lys genotype the highest level of the peptide in plasma is determined in patients with EH complicated by CHF. In owners of the Asn allele concentration of ET-1 in men with EH was significantly higher than in control subjects, but the difference between patients with EH was not found. In men with uncomplicated EH with LVH, who are carriers of Lys/Lys genotype the 2d degree of arterial hypertension (AH) is significantly more common, and in carriers of the Asn allele the 3d degree of AH. In patients with EH and CHF carriage of the Asn allele is associated with 3d degree of AH. Conclusions. Lys/Lys genotype and the Lys allele of the ET-1 gene dominate among control group and patients with EH. The carriers of the Asn allele of the ET-1 gene have significantly higher plasma levels of the aforementioned peptide among the control group and in the patients with EH. The Asn allele is associated with 3d degree of AH. The ET-1 boundary levels were estimated, that can be used for screening of large contingents of people for early diagnosis of EH and CHF.